IMPLEMENTASI PENGARUSUTAMAAN GENDER DALAM PEMBANGUNAN DI KABUPATEN KOTABARU - Edgar Bayu Refansyah; Hana Apriliani; Rachmat Hidayat (Berajah Journal, 2026)
Gender Mainstreaming is a development strategy aimed at realizing gender equality and justice through the integration of gender perspectives in policies, programs, and activities. This study aims to describe the implementation of Gender Mainstreaming in Kotabaru Regency, identify obstacles, and provide strategic recommendations. Previous research indicates that Gender Mainstreaming at the regional level is generally hampered by minimal institutional capacity, weak cross-sectoral coordination, and budget constraints. However, previous research tends to only highlight macro indicators without examining the sustainability of implementation. These weaknesses are the reason for this study, using gender mainstreaming and good governance theories as an analytical framework. Data collection methods include reference studies of policy documents and interviews with relevant stakeholders. The results show that despite the existence of a Regional Regulation on Gender Mainstreaming in Kotabaru Regency, the implementation of Gender Mainstreaming activities has not been consistent and significant, even halting in the 2023–2024 period. This condition indicates a gap between normative commitment and actual implementation, so that institutional strengthening, coordination across SKPD with vertical agencies and the community, and budget support are needed to ensure program sustainability.